2014
DOI: 10.5468/ogs.2014.57.6.436
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors affecting the timing of delivery in twin pregnancies

Abstract: ObjectiveTo investigate clinical factors affecting the timing of delivery in twin pregnancies in order to minimize perinatal complications.MethodsA retrospective study involved 163 twin pregnancies delivered from January 2006 to September 2011 at Gachon University Gil Medical Center. These cases were divided into three groups based on the delivery timing: less than 32 weeks' gestation (group A), between 32 and 35+6 weeks' gestation (group B), and over 36 weeks' gestation (group C). Clinical factors including m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Multiple pregnancies present a higher incidence of maternal and fetal adverse outcomes compared to singleton ones [ 3 , 9 13 ]. Twin pregnancies account for 12.2% of preterm births and 15.4% of neonatal deaths [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple pregnancies present a higher incidence of maternal and fetal adverse outcomes compared to singleton ones [ 3 , 9 13 ]. Twin pregnancies account for 12.2% of preterm births and 15.4% of neonatal deaths [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, out of total deliveries, 61.4% were preterm which is very similar to the study conducted by MD Michael O Gardner et al [10] in which 54% of twins were preterm compared with 9.6% among singletons. Chae Min Lee et al [11] in his study found that the mean duration of pregnancy for twin gestations was 29.5 weeks, and deliveries at less than 36 weeks were 76.1%.…”
Section: Discussionmentioning
confidence: 95%
“…This possibility is supported by the larger proportion of late preterm births among the prematurity population and the lower proportion of twins with birth weight discordance. In addition, in the case of twins, unlike that of singletons, the delivery time is determined according to chorionicity and amnionicity [ 12 , 13 ]. The American College of Obstetricians and Gynecologists suggested that obstetricians consider delivering twins in the preterm to early term according to their chorionicity.…”
Section: Discussionmentioning
confidence: 99%